PERBANDINGAN INHIBISI BRUSEIN D TERHADAP PROTEIN NFKB PADA SEL KANKER PANKREAS SECARA FLEKSIBEL DAN RIGID DOCKING - Harry Noviardi; Armi Wulanawati; Muhammad Sholehuddin malik Ibrohim (Sekolah Tinggi Teknologi Industri dan Farmasi Bogor, 2017)
Pancreatic cancer is a malignant tumor types are particularly deadly. Patients with pancreatic cancer are generally treated with chemoradiotherapy and gemcitabine, but still provide a good clinical outcome. This study aims to determine the ratio of the potential of bruceine D as inhibitors of protein NFĸB transcription of pancreatic cancer cells by the Gibbs free energy (ΔG), inhibition constants, hydrogen interactions are flexible and rigid docking. Based on the analysis docking, docking flexibly deliver better results than rigid. Additionally, bruceine D provides the potential for better inhibition than gemcitabine.